Towards more conflict-tolerant deontic logics by relaxing the interdefinability between obligations and permissions - Straßer, Christian; Beirlaen, Mathieu (2010)
While conflict-tolerant logics (CTDLs) usually allow for obligation- obligation conflicts, they fall short of tolerating obligation-permission con- flicts (OP-conflicts) of the type OA ∧ P¬ A. Moreover, for the sake of conflict-tolerance these logics usually do not validate the very intuitive principle (D), OA ⊃ PA. We demonstrate in this paper that by relaxing the interdefinability between obligations and permission PA =df ¬O¬A that is characteristic for most deontic logics, the logics get more conflict-tolerant since they allow for OP-conflicts. Moreover, this way they can be equipped with (D) without the need to sacrifice conflict-tolerance. In this paper we offer a generic procedure that transforms a given CTDL into a logic that tolerates OP-conflicts and validates (D).